Biochemical And Functional Properties Of Processed Flaxseed (Linum Usitatissimum) Flour (Applied Biological Research, 2017)
Flaxseed is a rich source of polyunsaturated fatty acids containing about 80% total oil with a high quantity of ω-3-fatty acids as well asmineral content. The objective of present study was to estimate the effect of different  processing treatments viz., roasting, defatting and combination of both on the  functional and biochemical properties of flaxseed flour. Flaxseed grains were  processed as full fat non-roasted flour, full fat roasted flour, partially  defatted roasted flour and partially defatted non-roasted flour. The results  revealed that partial defatting and roasting increased crude protein (34.0%),  ash (5.57%), crude fibre (12.34%) and total phenol (301.25 mg 100 g-1)  contents as well as antioxidant activity (92.3%) in flaxseed flour. However,  crude fat (37.7%), free fatty acid (0.37%), peroxide value (2.95 meq kg-1),  phytic acid (950.2 mg 100 g-1) and tannins (318.4 mg 100 g-1) were highest in  full fat non-roasted flour. Water absorption capacity (2.25 gg-1), foam  capacity (21.76%) and foam stability (84.6%) were higher in partially  defatted roasted flour. Based on functional and biochemical parameters  partially defatted roasted flaxseed flour was found best.
Keywords: Flax flour; foam capacity; foam stability; minerals; phytic acid; tannin